PENDIDIKAN MODERASI BERAGAMA DALAM PENGUATAN WAWASAN KEBANGSAAN - Dinar Bela Ayu Naj'ma; Syamsul Bakri (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This paper aims to explain the importance of strengthening religious moderation and national insight for the community through educational institutions, both formal, non-formal and informal educational institutions. This research is a qualitative research to find the meaning of a phenomenon. The data analysis uses the triangulation method, which is to cross check from a document source with another source, or from a document source with a historical fact. These results are (1) Formal educational institutions are the right means in carrying out religious moderation activities because in formal education there is a structured, systemic and easy-to-evaluate learning space, (2) religious moderation learning in non-formal institutions, is very effective in developing insight nationality considering that non-formal educational institutions are built on public awareness and are doctrinal in character, (3) the implementation of religious moderation education in informal educational institutions is also no less strategic considering that informal educational institutions that are integrated in the community can effectively stem radical religious beliefs that easily accessible and consumed by the public.Keywords: Religious Moderation; National Insight; Educational Institutions